Investment and risk appraisal in energy storage systems: A real options approach. (1st June 2016) - Locatelli, Giorgio; Invernizzi, Diletta Colette; Mancini, Mauro
Abstract: The increasing penetration of variable renewable energy is becoming a key challenge for the management of the electrical grid. Electrical Energy Storage Systems (ESS) are one of the most suitable solutions to increase the flexibility and resilience of the electrical system. This paper presents an innovative methodology for the appraisal of the investment in ESS. The methodology is based on the Real Option Analysis and is able to properly consider investment risks and uncertainties as well as the options available for the investor. The paper assesses the value of the option to wait for a change in the market conditions before investing and re-evaluates the profitability of the investment after each step of the development of the ESS project. In order to exemplify relevant results, this method is applied to the UK energy market and assesses the technical and economic feasibility of investing in ESS operating price arbitrage and Short Term Operating Reserves. The results show that the implementation of the Real Option Analysis increases the economic performance of ESS. Nevertheless, ESS still requires limited incentives to be economically viable. Highlights: Energy storage systems (ESS) can increase renewable power integration. We consider ESS investment risks and options to offset these risks. The real option analysis (ROA) values the waiting for a reduction of risks. The implementation of the ROA increases the economic performance of ESS. ESS requires limited incentives to be economically viable.